Milk Pie Production Management System in The MSME (UMKM) Sector in Denpasar (Case Study: UMKM CV. NAJWA) - Al Sabet, Fia Birtha (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
MSME (UMKM)s (Micro, Small and Medium Enterprises) are the driving force of the economy in Indonesia, especially in Denpasar. This can be seen from the large amount of state foreign exchange income coming from MSME (UMKM)s. In the last decade, many micro businesses have emerged, whether in the form of culinary businesses, fashion, agribusiness, and others. Research with the title